Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Kemampuan Komunikasi Mahasiswa pada Materi Pencemaran Udara dan Atmosfer - Asmiyunda, Asmiyunda; Sanova, Aulia (Universitas Negeri Padang, 2024)
This article explains how students' communication skills can be enhanced by using the jigsaw-style cooperative learning model with air pollution material and atmosphere content. The jigsaw-style cooperative learning model involves students working in small groups to achieve learning objectives. The purpose of this study was to enhance students' communication abilities in comprehending and conveying information about air pollution and atmosphere. Classroom action research (CAR), which is conducted over two learning cycles, is the research methodology employed. Students teaching environmental chemistry courses in their sixth semester made up the study's sample. The data analysis used was the non-parametric paired sample wilcoxon signed-rank test with the SPSS application and the effect size test with microsoft excel application. The research findings showed that there was a significant difference in the use of the jigsaw cooperative learning model to improve students' communication skills. The effect size of the increase was in the moderate category on the indicator of listening to information with a value of r = 0.39, communicating ideas clearly with a value of r = 0.63, and the interlocutor who understood the message with a value of r = 0.61. As a result, students' comprehension and communication skills regarding the air pollution and atmosphere increased with the development of a learning model that emphasizes cooperation and communication within the framework of environmental learning is significantly aided by this study.